From "can-do" girls to insecure and angry: affective dissonances in young women's post-recessional media. Issue 6 (18th August 2019) - Dobson, Amy Shields; Kanai, Akane
ABSTRACT: Feminist scholars have begun to unpack the ways in which neoliberalism is underpinned by particular gendered affective investments: drives for perfection, confidence, and the careful observance of feeling rules mandating a pleasing balance of resilience and approachability. In this context, we are interested in mapping the cultural production of affective dissonances with neoliberal modes of thriving. We draw attention to post-recessional television made by and about young women that articulate affective dissonances with the confident subjectivities associated with neoliberal cultural mythologies of girlpower. We suggest that within recent, largely USA, television some important questioning of such mythologies is taking place through the articulation of young women's anger, insecurity, anxiety, and misplaced confidence. Such affective dissonances may to some extent serve to problematise myths about both the accessibility and appeal of highly individualist career-oriented lifestyles idealised in cultural mythologies of powerful "can-do" girls. Our analysis aims at two-fold consideration of: first, how giving voice to young women as "suffering actors" may open space for dissonant affective positions that connect to feminist aims of social transformation; and second, consideration of the ways in which exclusionary technologies of femininity may also operate through representations of young women's anger, insecurity, and anxiety. Through this analysis we contribute to understanding dialectical tensions in the psychic and affective life of post-feminism and feminine subjectification in the neoliberal, post-recessional socio-cultural context.